The Internationalisation of Tobacco Control, 1950–2010. Issue 4 (15th September 2016) - Reubi, David; Berridge, Virginia
Abstract : This article explores the internationalisation of tobacco control as a case study in the history of international health regulation. Contrary to the existing literature on the topic, it argues that the history of international anti-smoking efforts is longer and richer than the making of the World Health Organisation's Framework Convention on Tobacco Control in the early twenty-first century. It thereby echoes the point made by other scholars about the importance of history when making sense of contemporary global health. Specifically, the article shows how the internationalisation of tobacco control started in the 1950s through informal contacts between scientists working on cancer research and how these initial interactions were followed by a growing number of more formal initiatives, from the World Conferences on Tobacco or Health to the Bloomberg Initiative to Reduce Tobacco Use. Rather than arranging these efforts in a linear narrative of progress culminating with the Framework Convention on Tobacco Control, we take anthropological claims about global health's uneven terrain seriously and portray a history of international tobacco control marked by ruptures and discontinuities. Specifically, we identify three successive periods, with each of them characterised by specific understandings of international action, tobacco control expertise, advocacy networks and funding strategies.